PROFESI DAN MICROTEACHING BERBASIS NILAI-NILAI ISLAMI - Zainal Asril (IAIN Padangsidimpuan, 2017)
Teacher is a profesi. In order to produce the professional teachers, some schools or universities have a micro teaching programs. It must be integrated with Islamic values. Teachers must be prepared become a professional teacher, they must have a range of skills, such as the skill to open the lesson, the skill to manage the class, and others. Besides, teacher must also have competencies; they are pedagogical competence, personalitty competence, professional competence, and social competence. Learning and Islam must be integrated to make good educators and students; in order to help them become better and better